An overview of fig biology and diversity - Othman, Halimaton Saadiah (Noor Publishing, 2021)
Fig (Ficus carica L.) is a member of Moraceae family, and it is the only species in the genus that is planted for fruit production. Fig is a hermaphrodite diploid that can be categorised with 4 types of fruit. Fig pollination is normally assisted through pollinator wasp known as Blastophaga psenes L. Major genetic erosion has posed a threat to fig germplasm over the last several decades. In order to overcome this, a few fig germplasm collections was established such as in North America, North Africa, Europe and Asia. Characterisation of fig cultivars are usually based on conventional methods which rely on phenotypic characterisation. This review describes the details involving fig biology as well as fig origin and diversity.